The perks of being a wallflower - Chbosky, Stephen (New York : MTV Books/Gallery Books, 2012)
A haunting coming of age novel told in a series of letters to an unknown correspondent reveals the life of Charlie, a freshman in high school who is a wallflower, shy and introspective, and very intelligent. It's a story of what it's like to grow up in high school, tracing a course through uncharted territory in the world of first dates, family dramas and new friends
"Now a major motion picture"--Cover
Keywords: High school students -- Social conditions -- Fiction; Bildungsromans; Teenagers -- Fiction; Letters -- Fiction; Diary fiction; High school students -- Fiction; Adolescence -- Fiction